(untitled) (Modern education and development, 2025)
Although the renal portal system is more prominent in lower vertebrates such as amphibians, reptiles, and birds, its concept remains relevant in understanding evolutionary anatomy and comparative renal physiology. In humans, the kidney does not have a classic renal portal vein, but the term is sometimes loosely used to describe venous structures related to renal drainage. This paper explores the anatomical and physiological aspects of the renal venous system, its clinical importance, and the concept of the renal portal system in vertebrate evolution.